TRAVEL AND TOURS MANAGEMENT SYSTEM - HUMAN RESOURCE 4 (Core Human Capital, Compensation Planning, HR Analytics, Payroll) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The system HUMAN RESOURCE IV is composing of four modules it proposes to the company and business to speed-up the old process of every single transaction, when it comes to the module of CORE HUMAN MANAGEMENT it is easily to Create a Job, Set Job Vacancy, Termination in this module. On the 2nd module the HR analytics can easily view the statistical progress of employee by the use of charts and graphs to easily predict the result of the graphs and charts to be able to compare the level ratings. The 3rd moduleis Compensation Planning in this module it refers to the process of all the components in-terms of compensation package such as; wages, salaries, and benefits, the manner in which it will be given to the employees. The 4th and last module is Payroll this module can easily generate pay-slip to every employee. In this study it uses the agile methodology wherein it has taken the software development world by storm. It started based on the four core principles as outlined in the Agile Manifesto. First is plan, the development team had started the planning on how, what and where do the study, collaboration of ideas that shares knowledge on how to start the study through searching, and visiting other company to conduct an interview, seek an idea and come up with a plan to start the development of the system next is the design of a system by designing of UI, this will be the creation of the plan or convention for the construction of the project, wherein the development team combined the plan to assure the outcome of the whole process and action of the development System. The Agile Methodology where the project is useful and beneficial. Therefore, the Development team concludes that in this study the knowledge will be more extensive provided to the following modules and to achieve a better process of Human Resource IV. The Job Creation can create a job position that is needed in a department. The 201 Files can view all the information of every employee, Off Boarding you can view the records who are Terminated, Resigned and Leave. Every department has a Salary Planning View to the corresponding salary of every employee and views the position of employee, basic pay of employee, salary per year of employee, salary per month of employee, salary per day of employee, salary per hour of employee, overtime rate of employee, holiday rate of employee. The Employee Contribution views the government legal contribution (SSS, Pag-Ibig, Phil-health, Tax).
Keywords: core human, HR analytics, compensation planning, payroll